2014
DOI: 10.1177/1535370214536679
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the lung: Design and development of tissue engineered macro- and micro-physiologic lung models for research use

Abstract: Respiratory tract specific cell populations, or tissue engineered in vitro grown human lung, have the potential to be used as research tools to mimic physiology, toxicology, pathology, as well as infectious diseases responses of cells or tissues. Studies related to respiratory tract pathogenesis or drug toxicity testing in the past made use of basic systems where single cell populations were exposed to test agents followed by evaluations of simple cellular responses. Although these simple single-cell-type syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 183 publications
0
75
0
Order By: Relevance
“…An overview of the available single-and multi-cell models of the lung is given elsewhere. (94,100,101) Recently, these cell culture models have matured into biomimetic models of the lung by incorporating previously neglected but crucial physiological aspects of the lung such as: 1) cultivation at the air-liquid interface with air on the apical side and liquid on the basal side of the epithelial barrier; (102,103) 2) growing the cells on biocompatible 3D (or 2D) matrices mimicking the elasticity of the pulmonary extracellular matrix; 3) exerting cyclic stretch on the cell layer simulating the mechanical strain profile experienced by the alveolar tissue during breathing activity; (104) and 4) combinations thereof. (105) FIG.…”
Section: Biological Models Of the Lungmentioning
confidence: 99%
See 1 more Smart Citation
“…An overview of the available single-and multi-cell models of the lung is given elsewhere. (94,100,101) Recently, these cell culture models have matured into biomimetic models of the lung by incorporating previously neglected but crucial physiological aspects of the lung such as: 1) cultivation at the air-liquid interface with air on the apical side and liquid on the basal side of the epithelial barrier; (102,103) 2) growing the cells on biocompatible 3D (or 2D) matrices mimicking the elasticity of the pulmonary extracellular matrix; 3) exerting cyclic stretch on the cell layer simulating the mechanical strain profile experienced by the alveolar tissue during breathing activity; (104) and 4) combinations thereof. (105) FIG.…”
Section: Biological Models Of the Lungmentioning
confidence: 99%
“…(101,108) The bottom-up approach is still in its infancy, but tremendous progress has been made in the past decade and tissue engineering holds great promise for substantially improving the availability and clinical relevance of future human lung models. (109) There are already several commercial providers for bioengineered biomimetic bronchial lung tissue reconstituted from primary human cells (e.g., Epithelix, Switzerland; MatTek Corp., USA), which closely resembles the human epithelial tissue of the respiratory tract.…”
Section: Biological Models Of the Lungmentioning
confidence: 99%
“…Attempts at creating more complex organ structures such as kidney or lung have proven more challenging, requiring accurate interactions between divergent cell types for function. For some organs, such as the lung, more than 40 cell types have been identified that require specific spatial positioning and cell-cell interactions to function properly (Nichols et al 2014). As the sophistication and precision of 3D-printing techniques improves, organs of higher complexity will be possible.…”
Section: Organ Printingmentioning
confidence: 99%
“…The respiratory tract, being the most sensitive entry port of nanomaterials, has been the focus of several hundred in vitro and in vivo studies [for reviews see (28)(29)(30)]. Therefore, it is not surprising that human advanced in vitro models have been developed in order to gain more insight into the mode of action of inhalable aerosols/(nano)particles ( Figure 1A, B).…”
Section: Cell-based In Vitro Models: the Bottom Up Approachmentioning
confidence: 99%